Association Between Rapid Antigen Testing and Antibiotic Use and Accuracy of Peripheral Blood Parameters in Detecting Group A Streptococcus in Children With Tonsillopharyngitis - Cag, Yakup; Özdemir, Abdurrahman Avar; Yükselmiş, Ufuk; Akdeniz, Ezgi; Özçetin, Mustafa (Frontiers in Pediatrics, 2019)
ABSTRACT Objectives: To investigate the effect of rapid antigen testing (RAT) on the practice of antibiotic prescription as well as the accuracy of peripheral blood neutrophil-to-lymphocyte ratio (NLR) and C-reactive protein (CRP) values in detecting group A beta-hemolytic Streptococcus (GABHS) in children with tonsillopharyngitis. Methods: In a multicenter study performed in Turkey, we retrospectively analyzed data from 668 consecutive pediatric patients under 17 years of age, who presented with signs and symptoms of tonsillopharyngitis and underwent RAT. The rates of positive and negative RAT results were determined and patients’ antibiotic prescriptions were examined in relation to RAT results. In addition, the accuracy of peripheral blood NLR and CRP values was examined for 212 patients whose laboratory data were available, with RAT as the reference standard. Results: Positive RAT results were observed in 190 of 668 (28.4%) patients. Antibiotics were prescribed to all 190 patients with positive RAT results and to 8 of 478 patients with negative RAT results. Overall, the rate of antibiotic prescription was 29.6%. Patients with positive and negative RAT results did not differ significantly with regard to NLR and CRP values. In ROC analysis, the area under the ROC curve (AUC) of NLR and CRP were 0.54 (95% confidence interval [CI] 0.45-0.64), and 0.55 (95% CI 0.45-0.65), respectively. Conclusion: RAT results proved highly associated with antibiotic prescribing, suggesting that RATs could be of great value in preventing unnecessary antibiotic use. Our findings also suggest that NLR and CRP are poorly accurate to identify GABHS in children with tonsillopharyngitis.